A Critical Approach to the Contemporary Regime of the Human Rights: About some conceptual and case-based contradictions. - Yépez Castro, José (2018)
The article provides a general critic over some fundamental contradictions found in the human’s rights regime. For that purposes, in a first part it criticizes some conceptual aspects of the human right practice. In a second part, it presents the well-known European case of the “crucifix”, to demonstrate how religion could influence the basis of a international court decision in a human right issue. In the same fashion, in the next part, the case of the treatment of property in the European Human Right System is analyzed. Equally important is the critique developed in the fourth part of the article to the self-determination right application nowadays. The essential conclusion of the article is that, despite the fact of the foundational morality of the human right regime, it is still significantly influenced by politics.